The Acculturation of the Qur'an and Javanese Culture: Variations in the Translation of the Word Khasar in the Tafsir Al-Ibriz by Bisri Musthofa - Ahmad Junaidi; Ahmad Isnaeni; Beko Hendro (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
Loss, whether material or non-material, is an inseparable part of the human experience that is constantly avoided. In a broader perspective, the concept of 'loss' extends beyond the loss of property, encompassing the loss of time, opportunity, and even faith. Despite being the most avoided thing, loss is often inevitable in life. Therefore, it is important to study this phenomenon in depth, especially from the perspective of the Quran as the primary source of guidance for Muslims. This study explores the acculturation of the Qur'an and Javanese culture through a linguistic analysis of the various translations of the term khasara (loss/ruin) in K.H. Bisri Musthofa's Tafsir Al-Ibriz. As a significant local Javanese commentary, Tafsir Al-Ibriz offers a unique lens to understand how Islamic sacred texts are contextualized within diverse cultural frameworks. Utilizing a qualitative methodology and library research, this study systematically inventories and analyzes 60 occurrences of khasara within the Qur'an, focusing on their interpretations in Tafsir Al-Ibriz. Findings reveal seven distinct translations for khasara in Tafsir Al-Ibriz: rugi, ngerugekake, tuno, ketunan, nunaake, kapitunan, and getun. Each translation is shown to carry specific semantic and pragmatic nuances rooted in Javanese cultural lexicon, transcending mere literal equivalents to convey deeper spiritual, ethical, and existential implications. This linguistic adaptation not only facilitates broader understanding among Javanese society but also demonstrates the dynamic interplay between divine revelation and local wisdom. The study concludes that K.H. Bisri Musthofa's Tafsir Al-Ibriz stands as a profound example of cultural adaptation in Qur'anic exegesis, highlighting how indigenous languages and cultural expressions can enrich the comprehension and internalization of religious teachings. This research contributes to the broader discourse on local tafsir traditions and the phenomenon of acculturation in Islamic intellectual history.